IMPLEMENTASI PERATURAN DAERAH KOTA PALEMBANG NOMOR 3 TAHUN 2015 TENTANG PENGELOLAAN SAMPAH RUMAH TANGGA DAN SAMPAH SEJENIS SAMPAH RUMAH TANGGA DI UNIT PELAKSANA TEKNIS TEMPAT PEMBUANGAN AKHIR SUKAWINATAN KOTA PALEMBANG (STUDI KASUS PASAL 16) - Heru Adi Putranto (STIA SATYA NEGARA PALEMBANG, 2022)
The Palembang City Regional Regulation Number 3 of 2015 hopes that the government will be able to help maximize the handling of existing waste problems. The results of initial observations made by researchers also found several indications such as the narrow road in the Sukawinatan Final Disposal Site Technical Implementation Unit so that garbage trucks had to queue to unload the garbage they carried, many garbage trucks were old and inadequate to operate and had not yet been carried out. adequate heavy equipment facilities are available so that garbage piles up highThe method used is a qualitative method, data collection techniques are carried out by means of observation, interviews with parties involved in becoming research informants, library research, documentation, and data analysis techniques.The results of the research on the implementation of the Palembang City Regional Regulation No. 3 of 2015 concerning the Management of Household Waste and Household-like Waste in the Technical Implementation Unit of the Sukawinatan Final Disposal Site in Palembang City (Case Study Article 16) has been carried out well because communication in handling waste to employees and to the public has been done with media circulars, banners and brochures. The existing human resources in handling waste at UPT Sukawinatan are sufficient. Facilities in waste processing are garbage pressing machine, 1 garbage chopper machine, 2 sewing machines, and PLTSA machines, 1 garbage motorbike which is operated in the Sukawinatan TPA area. Waste handling activities have been carried out by sorting the waste that enters the Sukawinatan TPA, Then the collected waste will be transported for later processing into compost or recycling. For the final process, waste that is not recycled and made into compost will be used as a source of methane energy for PLTSa. Keywords: Implementation of Waste Handling